High-Throughput Library Screening Identifies Two Novel NQO1 Inducers in Human Lung Cells - Tan, Xiang-Lin (American Thoracic Society, 2012)
Many phytochemicals possess antioxidant and cancer-preventive properties, some putatively through antioxidant response element–mediated phase II metabolism, entailing mutagen/oxidant quenching. In our recent studies, however, most candidate phytochemical agents were not potent in inducing phase II genes in normal human lung cells. In this study, we applied a messenger RNA (mRNA)–specific gene expression–based high throughput in vitro screening approach to discover new, potent plant-derived phase II inducing chemopreventive agents. Primary normal human bronchial epithelial (NHBE) cells and immortalized human bronchial epithelial cells (HBECs) were exposed to 800 individual compounds in the MicroSource Natural Products Library. At a level achievable in humans by diet (1.0 μM), 2,3-dihydroxy-4-methoxy-4′-ethoxybenzophenone (DMEBP), triacetylresveratrol (TRES), ivermectin, sanguinarine sulfate, and daunorubicin induced reduced nicotinamide adenine dinucleotide phosphate:quinone oxidoreductase 1 (NQO1) mRNA and protein expression in NHBE cells. DMEBP and TRES were the most attractive agents as coupling potency and low toxicity for induction of NQO1 (mRNA level, ≥3- to 10.8-fold that of control; protein level, ≥ two- to fourfold that of control). Induction of glutathione S-transferase pi mRNA expression was modest, and none was apparent for glutathione S-transferase pi protein expression. Measurements of reactive oxygen species and glutathione/oxidized glutathione ratio showed an antioxidant effect for DMEBP, but no definite effect was found for TRES in NHBE cells. Exposure of NHBE cells to H(2)O(2) induced nuclear translocation of nuclear factor erythroid 2–related factor 2, but this translocation was not significantly inhibited by TRES and DMEBP. These studies show that potency and low toxicity may align for two potential NQO1-inducing agents, DMEBP and TRES.